Effects Of Prostacyclın In Osteoclastıc Actıvatıon - Yalçın Işımer; Aşkın Işımer; İlter Uzel (Galenos Yayinevi, 1990)
The potential therapeutic value of the chemically stable prostacyclin analogue ZK 36 374 (Iloprost) was studied in osteoclastic activation during experimental orthodontic tooth movement. Twenty rats are divided into two groups of ten animals. The rats were anesthesized with pentobarbital sodium (i.p.) and suitable appliance was inserted beween the first molar and incisor of the mandibular to exert a pressure of 20 gr/cm2 0.01 ml. 25 ng/ml. Iloprost solution was injected for three days at 24 hour intervals into the submucosal area of the first molars mesial in the test group while 0.01 m. saline was injected in the control group At the third day, the mandibulary bones of the rats were dissected and stained. The number of osteoclasts was counte.In the test group, the Iloprost solution injected into the gingivalying near the first molar caused the appearance of osteoclasts and bone resorption. These results suggest that the prostacyclin plays a non-negligible role in the experimental othodontic tooth movements.